Access to Tuberculosis Treatment for Migrant and Refugee Populations in Tak province, Thailand - Tschirhart, Naomi (Université d'Ottawa / University of Ottawa, 2017)
Objectives: The aim of this project was to examine tuberculosis (TB) treatment access among migrant and refugee populations in a Thai border province. To study TB control from a wider perspective, we also sought to understand how migrant and refugee cases are enumerated in the public health surveillance system and explored treatment providers’ responsiveness to treatment barriers. Methods: We used a concurrent mix-methods design with an overarching qualitative emphasis and an embedded smaller quantitative survey. To gain perspectives on treatment accessibility we conducted focus group discussions with TB, tuberculosis and human immunodeficiency virus co-infection (TB/HIV) and multidrug-resistant tuberculosis (MDR-TB) patients. We also held key informant interviews with TB treatment providers and public health officials in Tak province and did a survey of community health volunteers. We analyzed the data using thematic analysis and descriptive statistics. Results: We found that migrants are travelling long distances with active TB to seek treatment in Tak province and that legal status influences migrants’ eligibility for TB care. Migrants in our study reported more barriers to accessing TB treatment than refugees. TB/HIV and MDR-TB treatment options for migrants in Tak province are limited and are heavily reliant on donor funding. We found that migrant and refugee TB cases are under reported in the public health surveillance system. Organizations in Tak province are highly collaborative and we identified two NGOs who have developed programs that are responsive to migrants’ needs. Conclusions: Our research suggests that in Tak province, Thailand access to TB treatment occurs at the intersection of health system accessibility, population ability and legal status. Interventions to improve treatment access and adherence to TB treatment necessarily extend outside of the healthcare system and address the social determinants of health.
Keywords: Tuberculosis; Migration; Migrants; Refugees; Thailand